Low estimated glomerular filtration rate and high body mass index are risk factors for acute kidney injury in systemic lupus erythematosus patients after cardiac surgery - Zhang, Xue; Wang, Chunrong; Tian, Yajie; Zhang, Yuelun; Miao, Qi; Wu, Di; Yu, Chunhua (Frontiers in Cardiovascular Medicine, 2024)
Objective: The occurrence of acute kidney injury (AKI) is common following cardiac surgery, especially among patients characterized with systemic lupus erythematosus (SLE), but studies on this clinical scenario have been limited by the rarity of SLE. We aimed to explore the risk predictors and outcomes with regards to postoperative AKI among cardiac-surgical patients concomitant with SLE. Methods: This was a single-center retrospective study performed in a tertiary hospital. Adult patients diagnosed with SLE who underwent cardiac surgery within the last 22 years were enrolled. Essential variables, including patient-, surgery- and anesthesia-related information, were collected from the medical record system. The definition of AKI was derived from the Kidney Disease: Improving Global Outcomes (KDIGO) criteria. Risk predictors suspected to be linked with post-surgical AKI were calculated using the univariable and multivariable analyses. Results: Of all 59 SLE patients undergoing cardiac surgery, 57 were ultimately enrolled into the analysis. AKI occurred in 29 patients (50.9%), who had significantly longer extubation time (median difference 1.0 day, P<0.001), ICU length of stay (median difference 2.0 days, P=0.001), postoperative length of stay (median difference 5.0 days, P=0.026), and more postoperative major complications (odds ratio 10.29, P=0.025) than the others. Preoperative estimated glomerular filtration rate (eGFR)<60 ml/min/1.73 m2 (odds ratio 5.31, P=0.021) and body mass index (BMI)≥24 kg/m2 (odds ratio 4.32, P=0.043) were the only two factors in the multivariable analysis that were significantly correlated with the development of postoperative AKI in patients with SLE after cardiac surgery. Conclusion: AKI in SLE patients after cardiac surgery is common and requires scrutiny, especially in overweight patients with moderate to severe preoperative renal dysfunction.